Case Report: Low-grade endometrial stromal sarcoma with intravenous and intracardiac extension: a case after misdiagnosis of endometrial stromal nodule as submucosal fibroid - Chai, Xiao-Shan; Tao, Guang-Shi; Ding, Hui; Zhou, Peng; Mei, Xi-Long; Li, Xiao-Xue (Frontiers in Oncology, 2023)
We present herein, a rare case of large vascular and cardiac metastases of Low-Grade Endometrial Stromal Sarcoma (LG-ESS)in a female patient , which occurred after misdiagnosis of endometrial stromal nodule (ESN) as submucosal leiomyoma seven years ago. Preoperative three-dimensional CT reconstruction was used to assess the extent of the lesion. The patient underwent radical resection: thrombectomy and total 2 hysterectomy with bilateral salpingo-oophorectomy without establishing the cardiopulmonary bypass. Intraoperative transesophageal ultrasound(TEE) was used to monitor whether the intracardiac mass was removed completely. To date, this patient is alive without any evidence of recurrence three years after surgery. The differential diagnosis of ESN and LG-ESS is often difficult. A clear distinction can only be reliably made after histological analysis of the tumor's entire interface with the neighboring myometrium. This case highlights that follow-ups of patients with ESN are important. Regular follow-up can detect metastasis and recurrence of misdiagnosed LG-ESS as early as possible. Distant metastasis of LG-ESS is rare, especially involving large vessels or the heart. The treatment should largely rely on multidisciplinary cooperation. Although the surgery is traumatic, the perioperative mortality rate is low, and patients can avoid death from congestive heart failure or sudden death.